2011
DOI: 10.2146/ajhp110125
|View full text |Cite
|
Sign up to set email alerts
|

Significant publications on infectious diseases pharmacotherapy in 2010

Abstract: Due to the increasing number of articles published each year, it is difficult to maintain a current knowledge of significant publications in the field of ID pharmacotherapy. This review of key publications in 2010 may be helpful to the nonspecialist clinician by lessening this burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Ref 1 (2) center within the preceding 30 days. The antimicrobial recommendation was based on a multicenter study that found high mortality rates in these patients due to multidrugresistant pathogens not covered by empirical antibiotics.…”
Section: Rankmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref 1 (2) center within the preceding 30 days. The antimicrobial recommendation was based on a multicenter study that found high mortality rates in these patients due to multidrugresistant pathogens not covered by empirical antibiotics.…”
Section: Rankmentioning
confidence: 99%
“…Am J Health-Syst Pharm-Vol 72 Aug 15, 2015 To continue previous efforts to identify and summarize important ID pharmacotherapy-related publications from the previous year, [1][2][3][4] HIDN members were asked to nominate articles published in 2014 that they believed had a significant impact on ID pharmacotherapy, including articles on human immunodeficiency virus (HIV) infection and acquired immunodeficiency syndrome (AIDS). All nominated articles were published between January 1 and December 31, 2014, in prominent peer-reviewed journals (e.g., Antimicrobial Agents and Chemotherapy, Clinical Infectious Diseases, Clinical Pharmacology and Therapeutics, Journal of the American Medical Association, New England Journal of Medicine).…”
mentioning
confidence: 99%
“…To support ongoing efforts to identify and summarize important recent ID pharmacotherapy-related publications, [1][2][3][4][5][6] HIDN members were asked to nominate articles published in 2015 that they believed had a significant impact on ID pharmacotherapy, including articles on human immu-nodeficiency virus (HIV) infection and acquired immunodeficiency syndrome (AIDS). All nominated articles were published between January 1 and December 31, 2015, in prominent peer-reviewed journals (e.g., Antimicrobial Agents and Chemotherapy, Clinical Infectious Diseases, Journal of the American Medical Association, New England Journal of Medicine).…”
mentioning
confidence: 99%
“…In an ongoing effort to identify and summarize significant publications on ID pharmacotherapy, [1][2][3][4][5][6] HIDN members were charged with compiling a list of articles published in 2013 that they believed had considerable impact on ID pharmacotherapy, including the management of human immunodeficiency virus (HIV) infection and acquired imLayar ar Am J Health-Syst Pharm-Vol 71 munodeficiency syndrome (AIDS). The articles selected were published in prominent peer-reviewed journals (e.g., Antimicrobial Agents and Chemotherapy, Clinical Infectious Diseases, Infection Control and Hospital Epidemiology, Lancet Infectious Diseases, New England Journal of Medicine, Science) between January and December 2013.…”
mentioning
confidence: 99%